Gene therapy in the putamen for curing AADC deficiency and Parkinson's disease - Paul Wuh‐Liang Hwu; Karl Kiening; Irina Anselm; David R Compton; Takeshi Nakajima; Thomas Opladen; Phillip L Pearl; Agathe Roubertie; Thomas Roujeau; Shin‐ichi Muramatsu (EMBO Molecular Medicine)
Abstract This commentary provides an overview of the putamen as an established target site for gene therapy in treating aromatic l‐amino acid decarboxylase (AADC) deficiency and Parkinson’s disease, two debilitating neurological disorders that involve motor dysfunction caused by dopamine deficiencies. The neuroanatomy and the function of the putamen in motor control provide good rationales for targeting this brain structure. Additionally, the efficacy and safety of intraputaminal gene therapy demonstrate that restoration of dopamine synthesis in the putamen by using low doses of adeno‐associated viral vector serotype 2 to deliver the hAADC gene is well tolerated. This restoration leads to sustained improvements in motor and nonmotor symptoms of AADC deficiency and improved uptake and conversion of exogenous l‐DOPA into dopamine in Parkinson’s patients.